Perkembangan Teknologi Tiktok Shop Sebagai Media Berbelanja Pada Mahasiswa Sosiologi Universitas Jember - Herdiana, Helen Dewi; Putri, Imelda Hartono; Aisyah, Lila (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Modernization in the Tiktok Shop feature which is a technological development, namely the presence of paperless payments made using a E-wallet. With the developments offered, this study aims to see whether emerging modernization can help to facilitate shopping activities carried out by students and seen using qualitative research methods with a phenomenological approach. The results found are that the modernization that has developed in the Tiktok Shop feature is very helpful for students in conducting an online buying and selling system.